Measuring the Resilience of Rural Banks Against COVID-19 Pandemic: Evidence from West Java, Indonesia - Wanda Kharisa Ristyanti (Jurnal Ekonomi Kuantitatif Terapan, 2024)
The potential disruption of operational activities in rural banks is linked to MSME actors'inability to repay loans amid the COVID-19 pandemic. The quality of credit and financingprovided by these banks is vital in ensuring income and interest continuity, thereby impactingprofitability. This study aims to analyze the financial performance dynamics and factorsinfluencing rural banks' profitability in West Java, Indonesia, during COVID-19. The researchutilized multiple linear regression with REM estimation. Despite the pandemic's challenges, theROA, CAR, and equity values of the rural banks met minimum standards, though NPL valuesexceeded maximum limits. The combined factors of CAR, NPL, equity, net income, and thepandemic collectively influence profitability. Specifically, NPL and the pandemic havesignificant negative effects, while net income positively impacts profitability. To bolster theresilience of rural banks during crises, suggested policy measures include strengthening capitalreserves, tightening credit policies, implementing good governance practices, and enhancingoperational cost efficiency.